The Influence of Training and Working Environment on the Performance of Nurses of Public Service Agency (BLUD) Inpatient Section of Ciawi Regional General Hospital (RSUD) - Pena; Samsuri; Ismartaya (International Journal of Management and Business Intelligence, 2024)
This study aims to determine the effect of training and work environment on the performance of Regional Public Service Agency nurses in the inpatient department at the Ciawi Regional General Hospital. The sample in this study was 65 people using a nonprobability sampling technique with purposive sampling technique, the research method used multiple linear regression with IBM SPSS software. The results of the validity and reliability tests show that all points of the statement are declared valid and reliable. The F test (simultaneous) states that there is a simultaneous positive and significant influence between training and the work environment on nurse performance. The results of the t test (partial) stated that training had a positive and significant effect on nurse performance and the work environment had a positive and significant effect on nurse performance at the Ciawi Bogor Regional General Hospital.